Differential Effects of Written Corrective Feedback on Iranian High School Students’ Grammatical Accuracy - Ali Roohani; Aliakbar Jafarpour; Hedayatallah Teimoori (Teaching English Language, 2015)
Prompted by the interaction hypothesis and focus on form instruction, corrective feedback has received much attention in recent years within the interactionist framework. This study investigated the effects of three types of written corrective feedback (i.e., recast without saliency, recast with saliency, and metalinguistic feedback) on Iranian high school EFL learners’ grammatical accuracy of two structures in English: conditional sentences and relative clauses. To this end, four intact classes, comprising 104 low-intermediate Iranian high school EFL learners, were selected and randomly assigned to experimental and control groups. The three experimental groups received recasts without saliency, recast with saliency, and metalinguistic feedback in written picture description tasks/activities. Grammaticality judgment tests were used as the instruments to collect data on the participants’ grammatical accuracy of the two structures in a pretest-posttest control group design. ANCOVA and MANOVA showed that using written corrective feedback significantly improved the participants’ grammatical gains in the experimental groups. Moreover, metalinguistic and recast with saliency feedback (i.e., explicit feedback) was more effective than the recast without saliency feedback (i.e., implicit feedback). Furthermore, there was a significant differential effect of metalinguistic feedback for the type of grammatical structure. The study concludes with several pedagogical implications.